Three-bottle exponential decay infusion: A novel intravenous infusion strategy for drugs which conform to three-compartment model with observations on propofol kinetics - Huang, Xiao-Hui; Xie, Hai-Tang; Kun, Wang; Huang, Ji-Han; Sun, Rui-Yuan (Bangladesh Journal of Pharmacology, 2012)
The aim of this study is to develop a novel three-bottle exponential decay infusion method to achieve the steady state concentration rapidly for drugs which conform to three-compartment model. The mathematical model and dosing regimen of three-bottle exponential decay infusion were developed. The input concentration of this method is a multi-exponential decay variable. With this method, blood concentration increased very rapidly to plateau value in the early phase of infusion and the target plateau concentration can be achieved much more quicker (approximately 10 to 35 times) than conventional constant rate infusion. This procedure was verified in rabbits and dogs and compared with conventional constant rate infusion with observations on propofol kinetics. This new quantitative methodology may provide a novel intravenous infusion strategy for drugs which conform to three-compartment model and can be used for the program design of infusion pump.